Lifestyles of the Rhiz and Not-So Famous : A Poetic Introduction to the Rhizosphere - Rayner, Lyndsay (MacEwan University Student eJournal, 2020)
The rhizosphere is a dynamic place where plant roots interact with soil, along with all of the living things that occupy this very small, yet very important space. Plants are often viewed as the foundation sustaining all living things on terrestrial Earth. But what about the components that sustain and impact our beloved chlorophyll companions? What helps them thrive? Where do the nutrients come from? What may potentially harm them? This collection of poems will help shine light onto the essential role that the microbial community plays on plant life and ecosystems at a global level.